Family Nursing Care During the COVID-19 Pandemic - Patungo, Viertianingsih; Thome, Angela Librianty; Nompo, Rifki Sakinah (KnE Life Sciences, 2021)
The COVID-19 pandemic can affect the health of a family. One of the effects is the change in interaction and communication patterns within a family. Nurses are required to have a perspective on family care needs, so indirectly the role of nurses to provide family care, communication and interaction must be well established. Communication is needed to build family resilience in responding to COVID-19. A literature review was conducted using electronic databases such as ProQuest and Pubmed. The search identified 9 relevant articles on family nursing care; while 2 articles address the main topic, 7 articles and 1 book were considered as supporting data. Family nursing care implements a component such as communication or conversation between nurses and families during the COVID-19 pandemic. The studies emphasize the importance of family nursing care during the pandemic, and stress the need for the nurse to understand and incorporate individual family circumstances into the discussion. This will allow them to help promote the optimal family functioning and protect the health of family members. Keywords: family, household, nursing care, COVID-19 pandemic